Fertility Restrictions and Life Cycle Outcomes: Evidence from the One-Child Policy in China - Huang, Wei; Lei, Xiaoyan; Sun, Ang (The Review of Economics and Statistics, 2021)
This study considers the experience of china's one-child policy to examine how fertility restrictions affect economic and social outcomes over a lifetime. Using variations in these penalties across provinces and over time, we find that exposure to stricter fertility restrictions when young leads to higher education levels, more white-collar jobs, delayed marriage, and lower fertility rates. Further consequences include lower rates of residing with the elderly and higher household income, consumption, and savings. Finally, exposure to stricter fertility restrictions in early life increases female empowerment. Overall, fertility restrictions imposed when people are young have powerful effects throughout their life cycle.